2023
DOI: 10.1038/s41598-023-35767-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cytotoxic effects of an extremely low-frequency electromagnetic field with doxorubicin on MCF-7 cell line

Abstract: Breast cancer is one of the leading causes of cancer deaths in women worldwide. Magnetic fields have shown anti-tumor effects in vitro and in vivo as a non-invasive therapy method that can affect cellular metabolism remotely. Doxorubicin (DOX) is one of the most commonly used drugs for treating breast cancer patients. It can be assumed that combining chemotherapy and magnetotherapy is one of the most effective treatments for breast cancer. This study aimed to investigate the potential cytotoxic effect of DOX a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In our PEMF system, treating cells with PEMF at 70 Hz and 2.5 mT showed no change in cell viability (Figure 1A). A recent paper has also shown that ELF-EMF at 50 Hz and 20 mT did not affect cell viability of MCF-7 cells [10] and the work of Loja et al [19] demonstrated that PEMF (15 Hz, 5 mT) did not change the growth of acute lymphoblastic leukemia and lymphoma cell lines. On the other hand, a previous study has revealed that cell viability of MCF-7 is impaired when exposed to PEMF at frequencies of 20~50 Hz and amplitudes of 2~5 mT [20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our PEMF system, treating cells with PEMF at 70 Hz and 2.5 mT showed no change in cell viability (Figure 1A). A recent paper has also shown that ELF-EMF at 50 Hz and 20 mT did not affect cell viability of MCF-7 cells [10] and the work of Loja et al [19] demonstrated that PEMF (15 Hz, 5 mT) did not change the growth of acute lymphoblastic leukemia and lymphoma cell lines. On the other hand, a previous study has revealed that cell viability of MCF-7 is impaired when exposed to PEMF at frequencies of 20~50 Hz and amplitudes of 2~5 mT [20].…”
Section: Discussionmentioning
confidence: 93%
“…PEMF also induced a significant increase in the apoptosis of etoposidetreated MCF-7 breast cancer cells [9]. Recently, there was a study reporting that treatment with extremely low frequency (ELF)-EMF can increase the cytotoxic effect of DOX on MCF-7 breast cancer cells compared with treatment with DOX alone [10].…”
Section: Introductionmentioning
confidence: 99%
“…Propidium iodide is effective in detecting DNA binding, specifically in dead cells HRT-1 within the cell population, as it cannot enter live cells because of intact membranes. In contrast, acridine orange can pass through cell membranes and bind to double-stranded DNA in live cells (Ramazi et al 2023).…”
Section: Apoptosis Assay Of Curle-ch Npsmentioning
confidence: 99%
“…Currently, standard treatments for most patients with lung cancer include surgery, chemotherapy, radiation therapy, targeted drugs, or a combination of these treatments 320 . Targeted drugs can work differently from chemotherapy drugs.…”
Section: Therapeutic Intervention Targeting Epigenetic Changesmentioning
confidence: 99%
“…Currently, standard treatments for most patients with lung cancer include surgery, chemotherapy, radiation therapy, targeted drugs, or a combination of these treatments. 320 Targeted drugs can work differently from chemotherapy drugs. Sometimes, when chemotherapy drugs are not more effective, they can work very well and also do not have the side effects of methods like chemotherapy.…”
Section: Therapeutic Intervention Targeting Epigenetic Changesmentioning
confidence: 99%